APPLICATION OF MOBILE LEARNING IN CLASS DISCUSSION - Ahmad, Nurbarirah; Sakarji, Siti Rosnita; Mohd Nor, Khalijah; Mohd Kodri, Aida Nur; Tewiya, Dr. Supaporn; Santhi, Dr. Natthaphon (Jurnal 'Ulwan, 2022)
Teaching is a challenging profession as it demands dynamic and creative ways to manage the learning process. To enhance that management of the learning process, technology has a great role to play in producing dynamic teachers of the present generation. It is expected that contemporary technology, such as mobile devices, will be seen in and integrated into today’s classroom. Mobile learning is defined as a learning medium that allows learners to use mobile devices to search and obtain materials anytime, anywhere, (Ozdamli and Cavus ,2013). Mobile learning uses mobile devices such as smartphones and laptops in an educational setting. This study examines gender roles in the use of online interaction or metalinguistic features in WhatsApp group amongst UiTM Melaka students. From these features, gender roles were noticeable, and they emphasize the concept of sex-role identification as an important and major factor in the development of gender differences. It is important to see how metalinguistic features have evolved today in view of gender roles in the WhatsApp group community to have a better understanding of the users’ behavior in building high self-efficacy levels. The aim of this study is to understand how different male and female users use metalinguistic features in weblogs. This is to enable the community to determine if a separate variety of metalinguistic features exists in the online community based on the distinctive form of discourse found within WhatsApp group.